Análise dialélica em populações F2 de soja para caracteres Fisiológicos e Agronômicos - Aline Cordeiro Taveira (2021)
Soybeans is a crop of great economic importance, with annual increase in production due to genetic improvement, which allowed its expansion to the most diverse regions, in addition to the improvement of several morphological characteristics of the crop, allowing for an increase in productivity. Breeding techniques seek to find and introduce characteristics of interest in commercial cultivars, among which diallel crossing stands out, widely used for selection of parents. Due to the need to increase soybean production in already cultivated areas, genetic improvement presents itself as one of the only tools capable of such a feat. Therefore, the objective of this work was to recommend promising parents for the improvement of physiological and agronomic characteristics of the soybean crop. Initially, eight contrasting soybean cultivars were selected in terms of physiological maturity and grain yield (Compacta, Spear, Zeus, M6410, NS6909, TMG7061, TMG7062 and TMG7063). The physiological characteristics evaluated were: net photosynthesis (A), stomatal conductance (gs), internal CO2 concentration (Ci) and transpiration (E). The agronomic characters evaluated were: days to maturity (DM), height of insertion of the first pod (AIV), plant height (AP), number of branches (NR), weight of one hundred grains (MCG) and grain yield (PROD). The best parents in relation to physiological characters were Compacta, Lança, M6410 and TMG7061. The best parents for agronomic traits were TMG7061, NS6909 and M6410. The best crosses for physiological traits were Compacta x Lança, Zeus x TMG7063 and M6410 x TMG7063. The best crosses for agronomic traits were Compacta x Spear, Compacta x TMG7062, Spear x TMG7062, Zeus x TMG7062, TMG7061 x TMG7062. Keywords: Specific combining ability. General combining ability. Glycine max. Genetical enhancement.